EFFECT OF HEALTH INFORMATION TECHNOLOGY ON REDUCING NURSES WORKLOAD IN EMERGENCY DEPARTMENT - Waleed Hamad Saleh Al Yami, Ali Abdulhafed Saleh Almomen, Hnadi Moubark M Alzogzog, Hussain Mohammed Saleh Alyami, Hussain Saleh Hadi Al mansour, Haya Hadi Saleh Al Makhalas, Abdullah Hassan Rashed Al Mansour, Ali Saeed Ali Alaklabi,; Sohairra Mosharea Rehan (Chelonian Research Foundation, 2023)
Introduction: The escalating demands on emergency department (ED) staff, particularly nurses, necessitate innovative solutions to reduce workload and enhance patient care. Health Information Technology (HIT) has emerged as a promising avenue to achieve these goals. This systematic review aimed to assess the impact of HIT on reducing nurses' workload in EDS, focusing on interventional studies and clinical trials conducted in the last few years up to 2022. Methods: A comprehensive search was conducted across PubMed, CINAHL, EMBASE, and the Cochrane Library, focusing on interventional studies and clinical trials from the last five years to 2022. Studies were included if they evaluated the impact Of HIT interventions (e.g., EHRs, CDSS, BCMA systems, and integrated monitoring systems) on nurses' workload in ED settings. The primary outcomes considered were reductions in documentation time, medication administration errors, and adverse drug events. Quality assessment and data extraction were performed systematically. Results: Eight studies met the inclusion criteria, encompassing a variety of HIT interventions. Key findings included a reduction in documentation time by up to 25%, medication administration errors by 45%, and potential adverse drug events by 50%. These results demonstrate the significant potential of HIT to enhance operational efficiency and patient safety in emergency care. However, the effectiveness varied based on the type of technology and implementation strategy, underscoring the need for tailored HIT solutions. Conclusions: HIT interventions significantly reduce nurses' workload and improve patient safety in EDS. The adoption of HIT, particularly EHRs, CDSS, BCMA systems, and integrated monitoring technologies, offers a viable strategy to address the Challenges faced by nursing staff in emergency settings. Future research should focus on overcoming implementation barriers and exploring the long-term benefits of HIT in diverse healthcare environments. Keywords: Health Information Technology, Emergency Department, Electronic Health Records, Clinical Decision .